THE DEVELOPMENT OF PEDAGOGY DEPARTMENTS IN HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTIONS (the beginning of the XX – the beginning of the XXI centuries) - Bashkir, Olha; Zolotuchina, Svitlana; Luparenko, Svetlana (Educological discourse, 2018)
The modern stage of education development in Ukraine calls for creating optimal conditions for effective implementation of the time-proven experience of professional teacher training in the work of the system of higher pedagogical educational institutions. The development of new forms and methods of education organization is impossible without learning and deep analysis of the accumulated experience of teaching staff training by Pedagogy departments. Thus, the aim of the article is to establish the stages of the development of these departments. With the help of the methods used by the author (historical structural, historical genesis, historical diachronic, historical comparative) there have been singled out the following stages of the establishment and development of Pedagogy departments in the structure of higher pedagogical educational institutions in Ukraine at the beginning of the XX – the beginning of the XXI centuries: the first stage (1921-1929 ) – the stage of organization of scientific-research departments of paedology and pedagogy as independent scientific-research centres; the second stage (1930-1957 ) – the stage of official recognition of the status of Pedagogy departments in the structure of higher pedagogical educational institutions; the third stage (1958-1990 ) – the stage of differentiating the profiles of Pedagogy departments in higher pedagogical educational institutions, their functions, areas of scientific and pedagogical activity; the fourth stage (1991 – the beginning of the XXI century) – the stage of Pedagogy departments integration under the conditions of the development of Ukrainian national pedagogical education. There has been found out and described the content details and tendencies of the scientific pedagogical activity of the departments at each stage. It has been specified that the stages of the department activity were singled out applying the following criteria: socio-economic and political changes during the researched period, which acted as objective factors for reforming higher pedagogical education; peculiarities of the government policy in the area of higher pedagogical education, which were reflected in the decrees and instructions by the Ministry of Education and assigned the role and place of Pedagogy departments in the system of higher pedagogical education; the range of tasks, realization of which required clear clarification of the content and tendencies of the activity of the departments under research.